Motives and satisfaction of followers of content aggregator @ussfeeds in consuming content - Richard Richard; Jandy Edipson Luik; Agusly Irawan Aritonang (Petra Christian University, 2025)
This study examines the motives and satisfaction of @ussfeeds followers in consuming content. The content referred to in this study focuses more on micro-news content. Micro-news itself is news uploaded on media but its content is shorter when compared to the source. As a content aggregator, @ussfeeds must be able to satisfy every follower's motive in the fields of current affairs, passing time, social utility, finance, salient, and entertainment. The research method used in this research is an online survey with an explanatory quantitative research type. The tests carried out in this study are validity and reliability tests, paired T tests, and cross tabulation. Through the six indicators proposed by Wohn & Ahmadi (2019) followers of @ussfeeds tend to be more satisfied in passing time, and salient. Through this study, it was found that @ussfeeds could not fulfill the motives in the other four indicators.